Pluralidad de concepciones en el pensamiento geográfico actual (Estudios humanísticos. Geografía, historia y arte, 1991)
A synthesis is offered of the changes that have taken place in Geography in the second half of this century - and innovative period of greater complexity for this discipline, which really appears as «new» as opposed to the «tradition», or earlier classic position.New tendencies, with afaster diffusion in the Anglo-Saxon schools of geography than in the others, were to follow, one after the other, from the fifties onwards ¿ those known as quantitative, theoretical, humanistic and radical are the best known and most relevant - However, following a lively and highly critical debate about each of these tendencies in previous years, there is now greater consensus and inter-relationship between them.